Comparison between clinical features and prognosis of malignancy- and non-malignancy-associated pediatric hemophagocytic lymphohistiocytosis - Hua Pan; Yongmin Huo; Lirong Sun (BMC, 2019)
Abstract Background The differences between the clinical characteristics and survival time in malignancy- and non-malignancy-associated secondary hemophagocytic lymphohistiocytosis (HLH) are unclear. Here, we describe the clinical characteristics, prognostic factors, and survival outcomes of malignancy-associated HLH compared to that of non-malignancy-associated HLH. Methods We retrospectively analyzed 91 pediatric patients with HLH (age < 14 years) at the Affiliated Hospital of Qingdao University Pediatric Department between January 2005 and October 2016. The patients were divided into the malignancy-associated group (n = 22) and non-malignancy-associated group (n = 69, also considered the control group). The clinical features were compared using the Mann-Whitney U and χ2 tests. The overall survival time was compared using log rank and Mann-Whitney U tests. Results Hemoglobin (HGB; p = 0.004), alanine aminotransferase (ALT; p = 0.002), and aspartate aminotransferase (AST; p = 0.001) levels in the malignancy-associated group differed from that in the non-malignancy-associated group. The mean survival times were 26.9 ± 3.82 months (malignancy-associated HLH) and 35.03 ± 2.19 months (non-malignancy-associated HLH). The overall survival time between the two groups was not statistically significantly different (p = 0.055). Univariate analysis showed that disseminated intravascular coagulation (DIC) score > 5 (p = 0.001), albumin < 25 g/L (p = 0.000), HGB < 60 g/L (p = 0.001), and platelet count (PLT) < 30 × 109/L (p = 0.042) correlated with prognosis. Multivariate Cox analysis showed that albumin < 25 g/L (p = 0.017), HGB < 60 g/L (p = 0.027), and bone marrow hemophagocytosis (p = 0.034) correlated with worse prognosis. Conclusions Patients with non-malignancy-associated HLH do not have better survival, although their prognosis is relatively better in clinical practice. A higher DIC score at diagnosis and lower albumin, HGB, and PLT levels are negative prognostic factors in malignancy-associated HLH.